Healthy dietary patterns and the incidence of chronic kidney disease: results from a prospective cohort study - Yong-Ping Lu; Bin Xia; Xiao-Hua Wang; Qiang-Sheng He; Chang-Bo Qu; Ying-Ying Xie; Tian-Jiao Cui; Si-Qing Wu; Jin-Yu Zhao; Zhi-Hua Zheng; Ting Zhu; Jin-Qiu Yuan; et al. (BMC Public Health)
Abstract Background Unhealthy diets contribute to the onset and progression of chronic kidney disease (CKD), with poor dietary habits identified as significant lifestyle factors that elevate CKD risk. Methods Data from the UK Biobank cohort, which included over 500,000 participants aged 40–69 from diverse regions of England, Wales, and Scotland, were analyzed. Participants, who completed at least one online 24-hour dietary recall assessment, were included in the study. The baseline for analysis was the first 24-hour dietary recall in 2011, with follow-up extending until the earliest occurrence of CKD diagnosis, death, or the end of the study period. Results A total of 207,268 British individuals who completed at least one online 24-hour dietary recall assessment were included in this study. Four healthy dietary pattern scores were evaluated: the Healthy Plant-based Diet Index (hPDI), the Healthy Eating Index (HEI)-2015, the Mediterranean Diet (MED) Score, and the Alternative Mediterranean Diet (AMED) Score. These scores assessed the association between dietary patterns and the incidence of CKD. Relative to the lowest dietary scores, the HR for CKD was 0.79 (95% CI, 0.73–0.87) for the hPDI, 0.80 (95% CI, 0.73–0.87) for the HEI-2015, 0.86 (95% CI, 0.81–0.93) for the MED, and 0.84 (95% CI, 0.78–0.90) for the AMED (all p < 0.001). Conclusion This study provides robust evidence linking healthy dietary patterns to a reduced risk of CKD. Further clinical trials are needed to confirm whether adherence to such diets can lower the risk of CKD.